Discovery of precise pH-controlled biomimetic catalysts: defective zirconium metal–organic frameworks as alkaline phosphatase mimics. Issue 23 (5th June 2019) - Xu, Ming; Feng, Liang; Yan, Li-Na; Meng, Sha-Sha; Yuan, Shuai; He, Meng-Jun; Liang, Hong; Chen, Xin-Yu; Wei, Hai-Yan; Gu, Zhi-Yuan; Zhou, Hong-Cai
Abstract : Defective zirconium metal–organic frameworks as artificial alkaline phosphatase mimics in precise pH-controlled biomimetic catalysis. Abstract : The well-controlled structural motifs of zirconium metal–organic frameworks (Zr-MOFs) and their similarity to enzyme cofactors make them ideally suited for biomimetic catalysis. However, the activation methodologies for these motifs, the structural information about active conformations and the reaction mechanism during these biomimetic reactions, are largely unknown. Herein, we have explored the precise pH-controlled activation processes, active sites, and reaction mechanisms for a series of Zr-MOFs as alkaline phosphatase mimics. Activation of the Zr-MOFs with a broad range and precise changes of pH led to the discovery of the MOF-catalyzed volcano plot with activity versus pH changes. This unique response revealed the existence of the precisely pH-controlled active form of the material, which was confirmed with computational analysis using density functional theory and diffuse reflectance infrared Fourier transform spectroscopy. These results will open a window for state-of-the-art design of efficient MOF enzyme mimics in aqueous solution.